2018
DOI: 10.5430/cns.v6n4p80
|View full text |Cite
|
Sign up to set email alerts
|

Rapid detection of Candida parapsilosis contamination in the infusion fluid

Abstract: We encountered a case of microbial contamination of infusion fluid detected based on the discoloration of an inline filter (membrane filter) in the main route. A cause of this contamination may be the use of an extension tube connected to the main route for more than a month. In the infusion fluid above the inline filter (on the high calorie end), 2.4 × 10 5 colony forming units (cfu)/ml of Candida parapsilosis was detected. "Adenosine triphosphate (ATP) + adenosine monophosphate (AMP)" was determined in addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…We previously reported that measurement of the adenosine triphosphate (ATP) level was useful as a simple method to evaluate infusion fluid contamination with microorganisms 17 , 37 . Since infusion fluid contamination can be estimated in a few minutes by measuring the ATP level, infusion fluid that is being administered should be checked using a simple detection method with ATP in patients in whom sepsis is suspected based on findings, such as a high procalcitonin level.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that measurement of the adenosine triphosphate (ATP) level was useful as a simple method to evaluate infusion fluid contamination with microorganisms 17 , 37 . Since infusion fluid contamination can be estimated in a few minutes by measuring the ATP level, infusion fluid that is being administered should be checked using a simple detection method with ATP in patients in whom sepsis is suspected based on findings, such as a high procalcitonin level.…”
Section: Discussionmentioning
confidence: 99%